THE WRITER AS TEACHER - Richler, Mordecai (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1969)
Having served a full term with the English lit. department at Sir George Williams University, in Montreal, as well as visiting the University of Toronto, and even venturing into the hurricane’s eye, Simon Fraser U., I’m now an authority on student unrest, the new militants, and the generation gap. An affluent society’s modish problems. I am also, suddenly, resentfully, thirty-eight years old, teeth loosening, hangovers more onerous, teetering on the precipice of middle-age, which naturally sours my conclusions. The student militants, though sometimes engaging, are mostly know-nothing paper tigers. Though they are served by the occasional inspired original teacher (and I honour no man more), they are also asked to endure too many professors who are mediocre and running embarrassingly scared.